Delirium Assessment in Acute Stroke: A Systematic Review and Meta-Analysis of Incidence, Assessment Tools, and Assessment Frequencies. (December 2019) - Stokholm, Jannik; Steenholt, Janni Vagner; Csilag, Claudio; Kjær, Troels Wesenberg; Christensen, Thomas
Purpose: The purpose of this systematic literature review was to examine whether different assessment methods contribute to the variance in delirium incidence detected in populations of patients with acute stroke. Specifically, the aim was to address the influence of (1) choice of assessment tool, (2) frequency of assessment, and (3) type of health professional doing the assessment. Methods: We searched MEDLINE, EMBASE, and PsycINFO and included pro- and retrospective cohort studies assessing delirium during hospitalization of adult acute stroke patients. Results: In 30 articles, 24 unique populations were identified and included in the review. Delirium incidence ranged from 1.4% to 75.6% in total and a chi-square test showed a significant heterogeneity across studies (χ 2 = 536.5, df = 23, P < .0001). No studies had an assessment for delirium before a patient entered the study. No specific patterns regarding the influence of tool, assessment frequency or health professional were discernible. Discussion: Subgroups analyses were not conducted due to the heterogeneity across studies. Studies comparing delirium assessment tools directly with each other are needed. Conclusions: Delirium is a common complication in acute stroke. No firm conclusions about a possible correlation of choice of tool, assessment frequency, and delirium incidence could be made due to the great heterogeneity of the study populations. Only 1 study compared 2 tools directly with each other. Further studies comparing delirium assessment tools directly with each other are needed.